Persepsi Guru Terhadap Perkembangan Sosial Emosional Anak - ., Azalia Arya Ramadhini; ., Masyunita Siregar; ., Tri Nurjanah; ., Arda Surya Reida; ., Yosi Nur Annisa Amanda; ., Sofia Sri Rezki (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
Early childhood education is a process that covers all aspects of child development from 0-6 years old. Social emotional development in children is preparing children to follow optimal learning. This research is quantitative descriptive. Simple random selection was used to select the sample for this study. Questionnaire / questionnaire is a tool used to research this research. Researchers distributed this questionnaire throughout Jambi province. Based on the discussion above, it was concluded that the teacher's perception of the child's social emotionality was quite good. Children are fully able to interact with their peers, children can express their opinions, children can put on and untie their own shoelaces, children are able to do their own tasks, children have empathy for their friends, and children can do toilet training themselves. as a whole, social emotional children at school have developed well